Macroeconomic uncertainty, inflation and growth: Regime-dependent effects in the G7 - Neanidis, Kyriakos C.; Savva, Christos S. (My University, 2013)
We analyze the causal effects of real and nominal macroeconomic uncertainty on inflation and output growth by considering whether these effects are cycle phase specific. Employing a bivariate Smooth Transition EGARCH-M model for the G7 countries during 1957-2009, we find strong nonlinearities. First, uncertainty regarding the output growth rate is related with a higher average growth rate mostly in a low-growth regime, supporting the theory of "creative destruction" Second, higher inflation uncertainty diminishes growth rates, mainly at a high-inflation regime. Finally, real uncertainty has mixed effects on average inflation, while the effect of nominal uncertainty is typically positive, especially so during inflationary periods. Our findings suggest that these relationships are sufficiently complex to require treatment with nonlinear models.
Keywords: EGARCH model; Uncertainty; Nonlinearity; Inflation; Output growth; Regimes